ANALISIS STRATEGI MENGHAFAL KOSA KATA (AL MUFRODAT) DI PONDOK PESANTREN UMAR BIN KHATTAB (UBK) U NTUK EFEKTIFITAS PEMBELAJARAN BAHASA ARAB - Feri Adnria; Afifudin Ahmad Robbani; Abdun Jamil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocabulary mastery (al-mufradāt) is one of the fundamental components in Arabic language learning because it significantly influences learners' listening, speaking, reading, and writing skills. However, many students encounter difficulties in memorizing and retaining Arabic vocabulary, which consequently affects the effectiveness of the learning process. This study aims to analyze the vocabulary memorization strategies implemented at Umar Bin Khattab Islamic Boarding School (UBK), Pekanbaru, and to examine their contribution to improving the effectiveness of Arabic language learning. The study employed a qualitative descriptive approach. Data were collected through classroom observations, semi-structured interviews with Arabic language teachers and students, and documentation of learning activities. The collected data were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings indicate that the boarding school implements several integrated vocabulary memorization strategies, including tikrār (repetition), talqīn (teacher-guided pronunciation), contextual vocabulary practice through Lisān al-'Arab, root-word (isytiqāq) analysis, vocabulary display media, and the establishment of an Arabic-speaking environment (bi'ah lughawiyyah). These strategies encourage students to memorize, comprehend, and actively use Arabic vocabulary in daily communication. The study concludes that the integration of systematic memorization strategies with a supportive language environment positively contributes to vocabulary acquisition and enhances the overall effectiveness of Arabic language learning at the Islamic boarding school.